Causality in Vietnam's parallel exchange rate system during 2005-2011: Policy implications for macroeconomic stability - Minh Tam Bui (Economies, 2018)
As in many transition economies, Vietnam has experienced a multiple exchange rate system with three exchange rates having co-existed. This paper uses the Vector-Error-Correction model and the Granger tests to investigate the relationship between the official and black market exchange rates from January 2005 to April 2011. The results confirm a long-run relationship between the official and parallel market rates of the Vietnam dong against the U.S. dollar. The short-run dynamics of two exchange rates suggest that the official exchange rate causes the black exchange rate, but not vice versa. This conclusion is valid for both a sub-period of stability and a sub-period of vibrant fluctuations, with February 2008 as the cut-off. The findings also reject the efficiency hypothesis of the black market for foreign exchange and support the policy choice of the State Bank of Vietnam not to follow black market signals in managing official exchange rates for macroeconomic stability.
Keywords: F31; E52; E58; C32; 330; parallel market; exchange rate dynamics; black market; causality; inflation